Death and the afterlife in Japanese Buddhism - Stone, Jacqueline Ilyse; Walter, Mariko Namba (University of Hawaiʻi Press, 2008)
"For more than a thousand years, Buddhism has dominated Japanese death rituals and concepts of the afterlife. The nine essays in this volume, ranging chronologically from the tenth century to the present, bring to light both continuity and change in death practices over time. They also explore the interrelated issues of how Buddhist death rites have addressed individual concerns about the afterlife while also filling social and institutional needs and how Buddhist death-related practices have assimilated and refigured elements from other traditions, bringing together disparate, even conflicting, ideas about the dead, their postmortem fate, and what constitutes normative Buddhist practice." "Death and the Afterlife in Japanese Buddhism constitutes a major step toward understanding how Buddhism in Japan has forged and retained its hold on deathrelated thought and practice, providing one of the most detailed and comprehensive accounts of the topic to date."--Jacket